بررسی رابطه بین کیفیت تدریس و خود تنظیمی تحصیلی میان محصلان پوهنتون تعلیم و تربیه کابل سال 1404 - Amini, Rahmatullah; Barz, Mohammad Jalal; Samadiar, Isar Ahmad (Farah Research and Scientific Journal, 2025)
The purpose of the present study is to examine the relationship between teaching quality and academic self-regulation among students of Kabul University of Education in the year 1404 (2025). This research is fundamental in nature and, in terms of data collection, falls under the category of correlational studies. The statistical population of this study consists of all students at the Kabul University of Education. The sampling method used in this research is cluster sampling. For data collection, two questionnaires were employed: the 38-item Teaching Quality Questionnaire (Rasouli) and the 30-item Academic Self-Regulation Questionnaire (Sowari & Arabzadeh). Data were analyzed using SPSS version 26. The findings of the study indicate that the correlation coefficient between teaching quality and academic self-regulation is (r = 0.499) at a significance level of (p = 0.00), suggesting a positive and significant relationship between the two variables. Therefore, it can be concluded that as teaching quality (including lesson planning, guidance and counseling, teaching skills, classroom management, and adherence to ethical considerations) improves, academic self-regulation also increases.